Impact of comorbid constipation on the survival of patients with heart failure: a multicenter, prospective cohort study conducted in Japan - Ishida, Tomoaki; Kawada, Kei; Jobu, Kohei; Hamada, Tomoyuki; Kubo, Toru; Okazaki, Moemi; Kawai, Kazuya; Nakaoka, Yoko; Yabe, Toshikazu; Furuno, Takashi; Yamada, Eisuke; Kitaoka, Hiroaki; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundConstipation frequently affects heart failure patients because of medication side effects and physiological effects of the condition. Although recent speculation suggests that comorbid constipation may affect cardiovascular disease onset and survival rates, this relationship remains unclear. We examined the effect of comorbid constipation on the survival of patients with heart failure.MethodsWe conducted a multicenter prospective cohort study (the Kochi YOSACOI study) of patients hospitalized for acute decompensated heart failure. The influence of comorbid constipation on survival was evaluated using Cox regression analysis with 2-year survival as the index. Patients were divided into two groups based on the presence of comorbid constipation. The patient background was adjusted using propensity score matching, and the evaluation included assessing the 2-year survival and cardiovascular mortality occurrence using the log-rank test.ResultsAmong 1,061 patients hospitalized for acute decompensated heart failure, 715 with complete data (124 with comorbid constipation and 591 without) were analyzed. Comorbid constipation was identified as a risk factor for poorer survival in the Cox regression model (hazard ratio: 1.90, 95% confidence interval: 1.3–2.8, P < 0.001). Propensity score matching included 104 patients in each group. Survival analysis using the log-rank test indicated worse survival (P = 0.023) and higher cardiovascular mortality (P = 0.043) in the comorbid constipation group.ConclusionConstipation can negatively affect the survival of patients with heart failure. Although the causal link between constipation and decreased survival remains unclear, identifying comorbid constipation is essential for identifying heart failure patients at a higher risk of poor outcomes.